Discharge Characteristics and Suspended Load from Rivers of Northern Indus Basin, Pakistan - Rehman, S. Shafiqur; Sabir, M. Amjad; Khan, Jehanzeb (Journal of Himalayan Earth Sciences, 1997)
An overview of the discharge and sediment load Of eight important rivers of North West Frontier Province is presented with a view to analyse the available surface water resource potential of this region most of which is originated from the northern Indus basin. The amount of total suspended solids being very high in most of the rivers have resulted in rapid silting and subsequent loss in the storage capacity of the existing reservoirs and it is time that priority is given to the construction of new dams.